2019
DOI: 10.1159/000497242
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Serum Vitamin D Levels and Health-Related Quality of Life in Maintenance Hemodialysis Patients

Abstract: Objectives: Aim of the study was investigating the effect of serum vitamin D levels on health-related quality of life in hemodialysis patients. Method: One-hundred and twenty-three maintenance hemodialysis patients were enrolled in this cross-sectional study. Patients divided into 2 groups according to serum vitamin D levels. A serum 25-hydroxyvitamin D (25[OH] D) level of < 20 ng/mL was identified as vitamin D deficiency (n = 78), and a serum level of ≥20 ng/mL was identified as normal (n = 45). Kidney Diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
4
7
1
Order By: Relevance
“…Kara In our study, we found that there was no significant correlation between comorbidity index, sex, and KDQOl-36. This finding was inconsistent with previous reports that have indicated a negative correlation between these parameters and HRQOL [35,36]. Since the Kt/V index of our patients was high (Kt/V> 2) and similar in both groups, no correlation was found between the Kt/V index and KDQOL-36.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Kara In our study, we found that there was no significant correlation between comorbidity index, sex, and KDQOl-36. This finding was inconsistent with previous reports that have indicated a negative correlation between these parameters and HRQOL [35,36]. Since the Kt/V index of our patients was high (Kt/V> 2) and similar in both groups, no correlation was found between the Kt/V index and KDQOL-36.…”
Section: Discussioncontrasting
confidence: 99%
“…Due to the presence of other factors capable of altering the results, we used multiple linear regression analysis to identify whether the independent effect of 25(OH) D. Although in the regression analysis, 25(OH) D level were statistically significant predictors of all KDQOL-36 subscales, it showed a particularly strong interaction with the burden of kidney disease and PCS subscales (p = 0.006 and p = 0.001). These findings were consistent with previous studies which suggested that dialysis patients with Vit-D deficient may have lower physical activity and a weaker mental activity [35,36]. However, it is required further research on this issue…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Few studies have evaluated the QOL scores in HD patients and reported poor QOL in these patients. [12][13][14][15][16] Ibrahim and El Salamony evaluated 60 HD patients in Egypt and reported that their QOL scores were poor (<50 score in all domains). They also found that the high prevalence of depression in these patients was associated with poor QOL.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond its function on calcium-phosphate metabolism, vitamin D exerts several pleiotropic effects [ 10 ]. Vitamin D regulates sleep directly and indirectly, and mounting evidence recommends a connotation between sleep disorders and hypovitaminosis D [ 11 ].…”
Section: Introductionmentioning
confidence: 99%